Migrants and access to healthcare: the Italian public health residents action plan. (13th November 2019) - Mammana, L; Milani, C; Bordin, P; Del Riccio, M; Sisti, L G; Salvia, C; Raguzzoni, G
Abstract: Background: Fighting health inequalities have been included in the WHO Sustainable Development Goals as a priority. Migrants are between the most vulnerable individuals and healthcare interventions, also during the post-migration period, should be oriented, context-specific and aimed at identifying reasons underlying inequalities, as suggested by the recent WHO report 'No public health without migrant health'. The "Inequality Working Group" of the Italian network of public health (PH) residents of the Italian Society of Hygiene, Preventive Medicine and Public Health (SItI) aims at identifying an interdisciplinary approach suitable to detect barriers to healthcare access for migrants in different Italian regions. Secondly, we aspire to develop some strategies to overcome unequal healthcare access. Methods: Focus group methodology was applied to set working group educational needs, priorities of action and working plan. Moreover, we implemented a network between various professionals involved in migrant healthcare, particularly with the Regional Groups of the Italian Society of Migration Medicine (SIMM). Results: After a period of peer-to-peer education about social determinants of health and migration, we reviewed Italian policies about migrants' healthcare and considered potential discrepancies from WHO recommendations. Furthermore, we mapped practices regarding access to care for migrant population and we focused on causes underlying unequal healthcare access. Conclusions: Although with regional differences, migrants have limited access to healthcare services and therefore represent a vulnerable subpopulation. Key messages: Fighting against the barriers that limit access to care for migrants is a priority for health systems. PH residents have a relevant role in identifying and defining critical issues, designing enforcement measures and implementing advocacy actions.